(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Insect pests that may significantly reduce production are a persistent threat to plants. The use of "omic" technologies and their application in research on the interactions between plants and sap-sucking insects will be succinctly summarized in this article. We discuss recent findings in this area and propose that insect mutualists may play a more significant role than is currently recognized as ’hidden actors’ in insectplant interactions